The Quantum Leap of Computing: Catalyzing a Paradigm Shift in Industrial Robot Adoption within Firms - Du, Xuegong; Wang, Yanping (Transformations In Business & Economics, 2025)
With the establishment of supercomputing centers in various regions and countries, the leap in computational power has become a reality. As a typical sign of firms’ move towards intelligence and digitalization, firms’ application of industrial robots holds significant importance in firm development. To explore the logic of industrial robot applications and the role of supply chain finance in them, utilizing the OLS fixed-effect model and drawing on the theories of technological innovation and resource-based view, and using the data of Chinese A-share listed companies from 2007 to 2023, the impacts of computational power leap on the application of industrial robots in firms were examined. Results indicate that the leap in computational power significantly enhances the application level of industrial robots in firms. Further analysis reveals that the leap in computational power can significantly boost firms’ intelligence levels, thereby promoting the application of industrial robots. Additionally, effective supply chain finance support can further strengthen the positive relationship between computational power leaps and the application of industrial robots in firms. The conclusions not only enrich the studies on firm intelligence development but also provide important empirical evidence for fully leveraging the value effect of computational power leaps and accelerating the intelligent process of firms.